Escape and Reconciliation of the Characters in the Short Story 'Tenggelam’ by Neneng Fatimah: A Psychological Analysis - Sofia, Risnawati; Rudi Adi Nugroho; Nurulrabihah Mat Noh (Universitas Negeri Semarang, 2025)
This research analyses the escape and reconciliation of the main character in the short story ‘Tenggelam’ by Neneng Fatimah using Rollo May's existentialist psychology approach and Sigmund Freud's literary psychology. The method used is qualitative with a descriptive approach. Researchers repeatedly read the story to identify mental and emotional dynamics and self-defense mechanisms and resolve the main character's inner conflict. The results showed that the main character's escape involved anxiety, guilt, and a form of love. This escape is realized through self-isolation and rejection of interaction with the surrounding environment, reflecting the character's efforts to deal with inner conflict and search for the meaning of his life. Reconciliation begins to appear when the main character faces the reality of his life with courage and accepts his condition. This reconciliation becomes the peak of emotional transformation, shown through accepting reality and building better relationships with people around her. This research is expected to contribute to the study of literary psychology by highlighting how characters' inner conflicts can be analyzed through a psychological perspective and the relevance of the theme of escape and reconciliation in the context of human life in general. The findings enrich the understanding of the relationship between literature and individual psychological dynamics.